2019
DOI: 10.1101/736892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary findings of single session of noninvansive brain stimulation over parietal lobe and performance on spatial memory task

Abstract: Spatial memory relies on efficient encoding, storage and retrieval of spatial information, which enables us to remember paths or locations of objects in everyday life. Moreover, this type of memory has been shown to decline with age and various neurodegenerative disorders. Parietal cortex has been shown to play an important role in the formation of short-term representations of spatial information. The aim of the current study was to test the possibility of immediate and long-term spatial memory enhancement, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Building up on that, tES studies showed that anodal stimulation of PPC leads to better AM of faces and words [39,40], as well as AM of objects and locations [39,41]. However, some studies did not find the modulatory effects of PPC-targeted transcranial direct current stimulation (tDCS) for AM-like functions [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Building up on that, tES studies showed that anodal stimulation of PPC leads to better AM of faces and words [39,40], as well as AM of objects and locations [39,41]. However, some studies did not find the modulatory effects of PPC-targeted transcranial direct current stimulation (tDCS) for AM-like functions [42][43][44].…”
Section: Introductionmentioning
confidence: 99%